Erratum to cardiac obstruction secondary to metastatic invasion - A rare complication of Human Herpes Virus 8-positive plasmablastic lymphoma in acquired immunodeficiency syndrome - Team, Editorial (Journal of Thoracic Disease, 2016)
In the article that appeared on Page 425–427, Vol 4, No 4 (August 2012) Issue of the Journal of Thoracic Disease (1), there is an error in the author’s name as “Sérgio Barros”. The correct name should be “Sérgio Barros-Gomes”.